UPAYA PENINGKATAN MUTU PENDIDIKAN AGAMA DI MADRASAH IBTIDAIYAH (SUATU KAJIAN TEORITIS-EMPIRIS) - Lobud, Sjakir (Hunafa: Jurnal Studia Islamika, 2007)
Religious education plays a remarkable role forÂ  developing humansâ morality. Therefore, in the National Development Â of Indonesia, religious education posses a chief position. This important position is implemented in schools throughout Indonesia, from elementary level to university level , both schools based on religious teaching and those based on secular one. For instance, at the elementary religious school, religious education has become one ofÂ  nationally-tested subject. However,Â  Islamic education at this level of education is considered to be abortive since pupils of this schoolÂ  are still unable to practice their religious teaching in their daily life. Based on this, efforts to enhance the quality of religious education at thisÂ  basic level of education must be made. What kinds of efforts should be made for that purpose, will be elaborated in this artikel. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Kata Kunci:Â  Mutu pendidikan agama, Madrasah Ibtidaiyah